2010
DOI: 10.1111/j.1365-294x.2009.04496.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive PCR reveals the complexity of postcopulatory sexual selection inTeleogryllus commodus

Abstract: The outcome of mate choice depends on complex interactions between males and females both before and after copulation. Although the competition between males for access to mates and premating choice by females are relatively well understood, the nature of interactions between cryptic female choice and male sperm competition within the female reproductive tract is less clear. Understanding the complexity of postcopulatory sexual selection requires an understanding of how anatomy, physiology and behaviour mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 71 publications
(104 reference statements)
0
47
1
Order By: Relevance
“…Indeed, the closer we get to fertilization, the less we understand about the mechanisms of cryptic female choice. Thus, we know more about female-mediated processes influencing intromission (e.g., Brennan et al 2007), sperm transfer (e.g., Sakaluk and Eggert 1996;Pilastro et al 2004;Bussière et al 2006;Hall et al 2010), and retention of sperm (e.g., Bishop et al 1996;Pizzari and Birkhead 2000;Dean et al 2011;Lüpold et al 2012) than we do about sperm storage and use for fertilization (e.g., Ward 1993;Otronen et al 1997;Có rdoba-Aguilar 1999;Fedina and Lewis 2004;Pattarini et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the closer we get to fertilization, the less we understand about the mechanisms of cryptic female choice. Thus, we know more about female-mediated processes influencing intromission (e.g., Brennan et al 2007), sperm transfer (e.g., Sakaluk and Eggert 1996;Pilastro et al 2004;Bussière et al 2006;Hall et al 2010), and retention of sperm (e.g., Bishop et al 1996;Pizzari and Birkhead 2000;Dean et al 2011;Lüpold et al 2012) than we do about sperm storage and use for fertilization (e.g., Ward 1993;Otronen et al 1997;Có rdoba-Aguilar 1999;Fedina and Lewis 2004;Pattarini et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Using "competitive PCR" (based on amplifying microsatellite markers) to quantify the relative contribution of sperm from two different males to the spermatheca in non-virgin females, however, Hall et al (2010) found that the proportion of sperm in storage for the second male to mate increased linearly with the duration of spermatophore attachment for that male in T. commodus. There is strong evidence that in G. bimaculatus ( Fig.…”
Section: T Oceanicusmentioning
confidence: 96%
“…11.2). Hall et al (2010) similarly quantified the relative amount of sperm in the spermatheca contributed by two males differing in the level of "attractiveness" (latency to copulation in precopulatory trials) in T. commodus. For a given duration of spermatophore attachment, Hall et al (2010) found that "attractive" males contributed more sperm to the spermatheca than "unattractive" males.…”
Section: Experimental Evidence Of Biases In Sperm Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…In T. dalmanni, Corley et al [74] suggest that differences in male fertility, patterns of sperm usage and ejaculate expenditure as a function of female reproductive value could explain extreme variations in paternity share. A recent study on Teleogryllus commodus field crickets [76] suggests a role for both sperm competition and cryptic female choice in determining reproductive success, highlighting the complexity of these post-copulatory interactions.…”
Section: Discussionmentioning
confidence: 99%